2019
DOI: 10.1111/fwb.13279
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation alters fatty acids in stream food webs

Abstract: Fatty acids are essential to macroinvertebrate growth and reproduction and can indicate food web structure and nutritional quality of basal resources. However, broad‐scale examinations of how catchment land cover and associated stressors affect the proportions of fatty acids (FAs) in stream food webs are few. Here, we: (1) examine relationships among proportions of FAs among benthic periphyton and macroinvertebrate collector/gatherers, shredders, and predators; and (2) test if relationships between periphytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The other ω3 PUFA, DHA, was low or absent in biofilms and invertebrates, and its functional role for invertebrate neural development may be fulfilled by EPA (Ahlgren et al, 2009;Stanley-Samuelson, 1994 (Guo et al, 2016a;Kühmayer et al, 2020;Torres-Ruiz et al, 2007), no matter whether EPA was from light or dark biofilms. Moreover, increased human disturbances in aquatic ecosystems, such as warming, eutrophication, riparian degradation and sedimentation (Burdon et al, 2013), are likely to decrease the availability of algal EPA for aquatic consumers (Guo et al, 2015;Hixson & Arts, 2016;Müller-Navarra et al, 2004;Whorley et al, 2019). In streams with high-nutrient inputs and high levels of removed riparian vegetation, algal communities in light biofilms can become dominated by filamentous green algae (deficient in EPA; Mosisch et al, 2001), whereas in dark biofilms, which are shaded and perhaps cooler from subsurface flows, a higher proportion of diatoms (rich in EPA) is expected (Mosisch et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The other ω3 PUFA, DHA, was low or absent in biofilms and invertebrates, and its functional role for invertebrate neural development may be fulfilled by EPA (Ahlgren et al, 2009;Stanley-Samuelson, 1994 (Guo et al, 2016a;Kühmayer et al, 2020;Torres-Ruiz et al, 2007), no matter whether EPA was from light or dark biofilms. Moreover, increased human disturbances in aquatic ecosystems, such as warming, eutrophication, riparian degradation and sedimentation (Burdon et al, 2013), are likely to decrease the availability of algal EPA for aquatic consumers (Guo et al, 2015;Hixson & Arts, 2016;Müller-Navarra et al, 2004;Whorley et al, 2019). In streams with high-nutrient inputs and high levels of removed riparian vegetation, algal communities in light biofilms can become dominated by filamentous green algae (deficient in EPA; Mosisch et al, 2001), whereas in dark biofilms, which are shaded and perhaps cooler from subsurface flows, a higher proportion of diatoms (rich in EPA) is expected (Mosisch et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For the other fauna, we found that fish and crustaceans had significantly higher contents of PUFA relative to periphyton. In the absence of de novo production, consumers may be more general in their feeding in order to ensure adequate consumption of necessary lipids or are retaining certain PUFA relative to the resource base (Guo et al, 2016; Sanchez and Trexler, 2018; Whorley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Consumers are dependent on a suite of PUFA for growth and health that are largely produced only by primary producers (Taipale et al, 2009). Therefore, changes in algal species composition will alter the relative abundances of important PUFA which could have negative bottom‐up effects on consumers (Galloway and Winder, 2015; Whorley et al, 2019). For example, loss of eukaryotic algae for bacteria, cyanobacteria, or detritus will be reflected in declines of important PUFA, notably n‐3 and n‐6 FA families, for organic matter rich in branched, methylated, or monounsaturated FA (MUFA) (Bossio et al, 2006; Vestal and White, 1989; Willers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Novel benthic invertebrate monitoring metrics could build on these ideas to emphasize the proportion or abundance of individuals with flying adult stages in future monitoring efforts. Measures that directly quantify the timing and amount of insect-mediated energetic subsidies from streams and lakes across a spectrum of watershed-scale stressors-while giving appropriate weight to the importance of insects that provision higher levels of nutritional macromolecules (such as fatty acids; Whorley et al, 2019) to riparian consumers-could also be useful in predicting potential consequences of poor water quality for terrestrial insectivores.…”
Section: Consequences Of Losing Aquatic-terrestrial Connections Via Imentioning
confidence: 99%